O052 Association of co-morbid insomnia and sleep apnoea (COMISA) symptoms with all-cause mortality: Analysis of the NHANES 2005-2008 data. (9th November 2022) - Sweetman, A; Lechat, B; Appleton, S; Reynolds, A; Adams, R; Melaku, Y
Abstract: Introduction: Co-morbid insomnia and sleep apnoea (COMISA) is a highly prevalent condition associated with negative health outcomes. This population-based study aimed to investigate the association between COMISA and all-cause mortality. Methods: Sleep data in 6, 877 participants (Age median [IQR]=45 [33, 57], 50.1% male) were drawn from the National Health and Nutrition Examination Survey (2005-2008). Insomnia was defined as difficulties initiating sleep, long awakenings, and/or early morning awakenings on ≥16 nights/month, with daytime impairment. The STOP-Bang questionnaire was used to identify participants at high risk of obstructive sleep apnoea (OSA). COMISA was defined if participants met criteria for insomnia and high risk of OSA. The median (IQR) follow-up for mortality was 8.6 (7.8, 9.8) years. Cox regression models were used to determine the association between COMISA and all-cause mortality, controlling for socio-demographic characteristics, behavioural factors and chronic conditions. Results: The prevalence of no insomnia/OSA, insomnia-alone, OSA-alone, and COMISA were 73.5, 3.0, 20.1, and 3.3%, respectively, and 6.7% of participants died by 11-year follow-up. Compared to participants with no insomnia/OSA, higher mortality risk was observed in participants with COMISA (HR=1.9; 95%CI=1.3-2.8) and insomnia alone (HR=1.5; 95%CI=1.0-2.3) after adjusting for socio-demographic characteristics, and behavioural factors. The relationship between COMISA and mortality persisted after additionally controlling for chronic conditions, sleep duration and sleeping pill use (HR=1.6; 95%CI=1.1-2.3), but the relationship between insomnia-alone and mortality did not (HR=1.4; 95%CI=0.9-2.3). Discussion: Co-morbid insomnia and high-risk OSA is associated with increased risk of all-cause mortality. More research is needed to identify effective treatments for COMISA.